2019
DOI: 10.1038/s42004-019-0115-6
|View full text |Cite
|
Sign up to set email alerts
|

Cupric-superoxide complex that induces a catalytic aldol reaction-type C–C bond formation

Abstract: Much recent attention has been focused on the structure and reactivity of transition-metal superoxide complexes, among which mononuclear copper(II)-superoxide complexes are recognized as key reactive intermediates in many biological and abiological dioxygenactivation processes. So far, several types of copper(II)-superoxide complexes have been developed and their electrophilic reactivity has been explored in C-H and O-H bond activation reactions. Here we demonstrate that a mononuclear copper(II)-(end-on)supero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…Recently, the first example was reported of a nucleophilic copper superoxide inducing a catalytic aldol reaction, that is, with acetone, forming 4‐hydroxy‐4‐methyl‐2‐pentanone at room temperature . In this context, the isolation of diacetone alcohol (4‐hydroxy‐4‐methyl‐2‐pentanone, Scheme ) as a side product in the course of the formation of [ 5 ] motivated us to test the two complexes [( L 1 Cu) 2 ](PF 6 ) 2 and [ L 2 CuO 2 ]PF 6 in dioxygen activation in terms of the catalytic conversion of acetone.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the first example was reported of a nucleophilic copper superoxide inducing a catalytic aldol reaction, that is, with acetone, forming 4‐hydroxy‐4‐methyl‐2‐pentanone at room temperature . In this context, the isolation of diacetone alcohol (4‐hydroxy‐4‐methyl‐2‐pentanone, Scheme ) as a side product in the course of the formation of [ 5 ] motivated us to test the two complexes [( L 1 Cu) 2 ](PF 6 ) 2 and [ L 2 CuO 2 ]PF 6 in dioxygen activation in terms of the catalytic conversion of acetone.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, both complexes mediate acetone dimerization to form 4‐hydroxy‐4‐methyl‐2‐pentanone, similar to a recently reported nucleophilic Cu 1 S E complex . Studies on the reactivity of the complex [( L 2 )Cu(O 2 )] + , which is stable for minutes at low temperatures, as a potential nucleophile are currently underway in our laboratories.…”
Section: Discussionmentioning
confidence: 99%
“…20,[22][23][24][33][34][35][36][37][38][39][40][41][42] While synthetic Cu(II)superoxo complexes have been characterized, [35][36][37]40,41 well-characterized end-on examples in a monooxygenase-like N3 T-shaped ligand geometry are comparatively rare. 24,38,43 These bioinspired Cu systems have also been applied to alcohol oxidation and hydroxylation reactivity, but in these cases thorough observation or characterization of discrete intermediates, such as Cu-superoxo complexes, is often not possible; detailed characterization on unifying intermediates such as Cu-superoxo complexes is lacking generally for catalytic systems. 17,18,24,44 Thus, while enzyme model complexes enable the isolation of putative catalytic intermediates, these model systems are typically not competent catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…In support of this scarcity, there has been only one example of a catalytic transformation mediated by a well-characterized Cu-superoxo complex, and we note this example is a redox-neutral aldol coupling. 43 Conversely, thoroughly characterized superoxo intermediates in aerobic catalysis have been observed in Mn, Fe, and Co-based systems which makes the rarity of similarly observable species in the ubiquitous aerobic catalysis of Cu even more notable. [45][46][47][48] We have recently been interested in using biomimetic approaches through dihydrazonopyrrole (DHP) ligand scaffolds that can support H + , e − , H-atom, or H2 transfer similar to biological cofactors or active sites.…”
Section: Introductionmentioning
confidence: 99%
“…As seen in the metalloenzymes, the rigid ligand environment imposes a specific coordination geometry on the copper metal center to control the reactivity of LCu II -OOR species. Such a coordination geometry given by the rigid ligand environment is called an entatic state. Comba et al and Funahashi et al independently examined the ligand effects on the reactivity of copper complexes using rigid bispidine-based bicyclic diamine ligands. We have also demonstrated that the rigid cyclic diamine framework of the ligands has a great impact on the O 2 reactivity of copper­(I) complexes. In this study, we have examined the reactivity of copper­(II) complexes with m -chloroperbenzoic acid ( m -CPBA) using a series of linear tetradentate N 4 ligands consisting of a 6-, 7-, or 8-membered cyclic diamine with pyridylmethyl (−CH 2 Py) side arms (Chart ) to evaluate the geometric effects on the reactivity of the copper­(II) acylperoxide complexes.…”
Section: Introductionmentioning
confidence: 99%